On the question of polygamy and debauchery of Prince Vladimir Svyatoslavich - Polyakov, Aleksandr Nikolaevich (Genesis: исторические исследования, 2022)
The subject of this study is the family ties of Prince Vladimir Svyatoslavich. The object is the personality of Prince Vladimir. The purpose of this article is to establish, based on a comparative analysis of sources, the degree of reliability of the facts they contain about promiscuity, the number of marriages and children of Vladimir. A materialistic approach to history is used as a methodological basis. Within its framework, the article applies: the comparative historical method, the method of critical analysis, the principles of historicism and objectivity. The source base is the data of the Russian chronicles ("The Tale of Bygone Years", the Laurentian Chronicle), the Chronicle of George Amartol, biblical texts, the writings of Titmar of Merseburg, Leo the Deacon, John Skilitsa, Ibn Haukal. The article discusses the controversial issue of Prince Vladimir's family ties. The author comes to the conclusion that Vladimir Svyatoslavich, contrary to the instructions of the chronicle on the prince's polygamy in the pagan era, was married only twice — the first time by a pagan marriage to the Polotsk Princess Rogneda and the second time by a Christian marriage to the Byzantine princess Anna. The number of the prince's children exceeded the figure indicated in the chronicle — about 8 sons and 9 daughters. The main "antihero" of ancient Russian history, Prince Svyatopolk, according to the author, was the legitimate son of Vladimir, not Yaropolk. At the same time, the author believes that Vladimir was distinguished by intemperance in relationships with women and kept many concubines.